Glimpsing Indonesia’s Social Media Discourse: What Goes on During the Covid-19 Infodemic - Ronny, Rafi; Herdiansyah, Herdis; Panjaitan, Berton Suar Pelita (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2023)
The COVID-19 pandemic has led to an